Constructing Meaning: The Role of Aristotelian Ethos, Pathos, and Logos Through a Neurosemantic Lens - I. S. Mannesa, Muh. Nur Haq; Kuswanjono, Arqom (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2025)
This study integrates Aristotelian rhetoric (ethos, pathos, logos) with neurosemantics to examine meaning construction in the human brain. Using a conceptual analysis approach, it explores the neural mechanisms underlying ethos-, pathos-, and logos-based communication strategies. The findings indicate that integrating rhetorical elements with neurosemantics enhances communication effectiveness across various domains, including education, marketing, and political discourse. Ethos establishes credibility through the activation of the ventromedial prefrontal cortex (vmPFC), pathos fosters emotional engagement via the amygdala and insula, while logos strengthens logical reasoning through the dorsolateral prefrontal cortex (dlPFC). This study also highlights practical applications in language therapy and neuroscience-based communication design to optimize message delivery.